An aircraft boarding model with the group behavior and the quantity of luggage. (August 2018) - Tang, Tie-Qiao; Yang, Shao-Peng; Ou, Hui; Chen, Liang; Huang, Hai-Jun
Highlights: Introduce the quantity of luggage and the group behavior into the aircraft boarding process. Propose a boarding model with the quantity of luggage and the group behavior. Explore the influences of the quantity of luggage and the group behavior on the boarding efficiency. Abstract: A reasonable boarding model can effectively improve the boarding efficiency. Therefore, developing boarding models/strategies to improve the boarding efficiency has been an interesting topic in the air transportation. In this paper, we incorporate the group behavior and the quantity of luggage into the boarding process, and then develop an extended boarding model to investigate the effects of the two factors on the delay time and boarding time. The numerical results show that the quantity of luggage may make each passenger's boarding behavior more complex, while the group behavior can shorten some passengers' delay time and the total boarding time. The results can help administrators organize the boarding process and enhance the boarding efficiency.